Adsorption of fluoride ions by Zn-Al layered double hydroxides - Mandal, Sujata; Mayadevi, S. (Applied Clay Science, 2008)
Zn-Al layered double hydroxides (LDHs) with different molar ratios Zn/Al (0, 0.17, 0.34, 0.97, 3.47, proportional to) were prepared by the co-precipitation of chlorides, characterized and evaluated for their fluoride adsorption at room temperature from aqueous solutions. The fluoride adsorption of the as-synthesized LDHs was influenced by the chemical composition of the LDHs and ZA-11 (Zn/Al = 0.97) had the highest capacity for fluoride adsorption (1.14-4.16 mg/g). The adsorption increased after calcination of the LDH up to 500 degrees C. The equilibrium data were fitted to the Freundlich, Langmuir, and Temkin equations. The kinetics of fluoride adsorption followed the pseudo-second order model. (C) 2007 Elsevier B.V All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Layered double hydroxide

Cellulose supported layered double hydroxides for the adsorption of fluoride from aqueous solution - Mandal, Sujata; Mayadevi, S. (Chemosphere, 2008)
Cellulose supported layered double hydroxides (CSLDHs) were synthesized and tested for adsorption of fluoride in aqueous medium. Three samples of cellulose supported LDHs were synthesized by varying the LDH loading on cellulose. The raw cellulose, unsupported LDH and cellulose supported LDHs were characterized by XRD, SEM and BET surface area. Batch adsorption as well as fixed-bed column experiments were performed for determining the fluoride adsorption characteristics of CSLDHs. The fluoride adsorption properties of CSLDHs were found to be superior to that of reported adsorbents, including activated alumina and carbon nanotubes. Defluoridation capacity of the CSLDHs was 2-4 times higher than that of unsupported LDH. The cellulose supported LDH, CSLDH-50, having an LDH loading of 27% showed maximum fluoride uptake capacity (5.29 mg g(-1) of CSLDH, 25.18 mg g(-1) of LDH) in fixed-bed column study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; cellulose; Fluoride; Layered double hydroxide

Defluoridation of water using as-synthesized Zn/Al/Cl anionic clay adsorbent: equilibrium and regeneration studies - Mandal, Sujata; Mayadevi, S. (Journal of Hazardous Materials, 2009)
Zn/Al/Cl anionic clay has been synthesized by co-precipitation method and applied for adsorption of fluoride in aqueous medium. Equilibrium adsorption data were fitted to Langmuir, Freundlich, Temkin, and Generalized isotherm equations. Thermodynamic parameters like Delta G and Delta H values show the feasibility and exothermic nature of the adsorption process. Influence of solution pH and presence of other anions on fluoride adsorption by the clay has also been studied. Presence of carbonate in water was found to have an adverse effect on fluoride adsorption by the clay. pH(pzc) of the clay has been found to be 8.97. A two-step 1st order kinetic model was used to explain the fluoride adsorption kinetics of the as-synthesized clay. It was possible to regenerate the adsorbent with an aqueous solution of 0.01 M NaOH and the effect of regeneration on fluoride adsorption was reported up to five regeneration cycles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Isotherm; kinetics; Regeneration

Adsorption of fluoride from aqueous solution by alumina of alkoxide nature: batch and continuous operation - Kamble, Sanjay P.; Deshpande, Gunavant; Barve, Prashant P.; Rayalu, Sadhana; Labhsetwar, Nitin K.; Malyshew, Alexander; Kulkarni, Bhaskar D. (Desalination, 2010)
In this investigation, we report the adsorption potential of alkoxide origin alumina for defluoridation of drinking water using batch and continuous mode of operations. The effects of different operating parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and interfering ions (usually present in groundwater) were studied with a view to understand the adsorption behavior of the material under various conditions. A thermodynamic study shows that the adsorption of fluoride by alkoxide origin alumina is an exothermic and spontaneous process. The kinetic results showed that the fluoride sorption follows pseudo-second-order kinetics. The applicability of adsorbent in the field is also tested through column breakthrough studies. It has been observed that with an increase in the flow rate and initial fluoride concentration, the breakthrough curve becomes sharper and the breakthrough time and adsorbed fluoride ion concentration decrease. The breakthrough curve also becomes steeper as the bed height increases. The alkoxide origin alumina based adsorbent media can be used directly for field applications since it is also commercially available in granular form. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Alkoxide alumina; Breakthrough studies; Fluoride; Kinetic modeling

Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye

Removal of fluoride from aqueous solution by mesoporous silica nanoparticles functionalized with chitosan derived from mushroom - Srivastava, Anushree; Kumari, Madhu; Ramanathan, Alagappan; Selvaraj, Kaliaperumal; Prasad, Bablu; Prasad, Kumar Suranjit (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
In the present study, chitosan functionalized mesoporous silica nanoparticles have been synthesized. Chitosan derived from an edible mushroom, Agaricus bisporus was used during synthesis of chitosan functionalized silica nanoparticles. The functionalized silica nanoparticles were subjected to fluoride sorption using a batch method which subsequently showed removal efficiency of 95% with maximum sorption capacity, 58.8 mg/g. The characterization of nanoparticles was carried out by SEM, EDAX, XRD and FTIR analysis respectively. EDAX analysis suggested that oxygen, 51.83% and silica 37.24% was main constituent of the functionalized nanomaterials. XRD yielded characteristic diffraction pattern corresponding to the lattice planes (100), (110), (112), (120), (200) and (220) respectively. Sorption data was used to study equilibrium isotherm namely Langmuir and Freundlich model. The adsorption capacity increased with temperature while kinetics studies revealed that the adsorption process followed a pseudo-second-order rate equation. The enthalpy change (Delta H) and entropy change (Delta S) was found to be -31.36 kJmol(-1) and -7.75 Jmol(-1) K-1, showing endothermic and spontaneous nature of the fluoride adsorption. Data suggested that the nature of adsorption belonged to chemisorptions. The overall results suggested that the synthesized nanoparticles showed strong and specific affinity for fluoride and could be excellent adsorbents for defluoridation.
Keywords: Adsorption; Chitosan; EDAX; Fluoride; SEM